A common tendency for phylogenetic overdispersion in mammalian assemblages - COOPER, NATALIE; RODRIGUEZ, JESUS; PURVIS, ANDY (The Royal Society, 2008)
Competition has long been proposed as an important force in structuring mammalian communities. Although early work recognised that competition has a phylogenetic dimension, only with recent increases in the availability of phylogenies have true phylogenetic investigations of mammalian community structure become possible. We test whether the phylogenetic structure of 142 assemblages from three mammalian clades (New World monkeys, North American ground squirrels and Australasian possums) shows the imprint of competition. The full set of assemblages display a highly significant tendency for members to be more distantly-related than expected by chance (phylogenetic overdispersion). The overdispersion is also significant within two of the clades (monkeys and squirrels) separately. This is the first demonstration of widespread overdispersion in mammal assemblages and implies an important role for either competition between close relatives where traits are conserved, habitat filtering where distant relatives share convergent traits, or both.
PUBLISHED
Keywords: NRI; net relatedness index; NTI; nearest taxon index; possum; squirrel; monkey; community phylogenetics